Recycling [videorecording] the endless circle - Brown, Roger; Costello, Job.; Lieberman, Douglas; National Geographic Society (Washington, D.C.). (Washington, D.C. The Society, 1992)
Examines both the problems causing our garbage glut and the ways that industries, communities and individuals are working to solve these problems. Explains recycling processes and describes how recycled plastic, papers, fibers and other materials can be used to create all kinds of new products.
VHS.
Credits : Narrator, Gene Galusha ; Editor, Jan Sutcliffe.
Keywords: Recycling (Waste, etc.).; Recycled products; Refuse and refuse disposal